The Subchronic Effect Of Water Extract Leaves Ofsoursop (Annona Muricata L.) Bax Expression Of Neuron Rat Hippocampus Gyrus Dentatus (Rattus Norvegicus) - Desnita Monica; Ety Sari Handayani (Al-Makki Publisher, 2023)
Soursop (Annona muricata) is a plant that is rich in benefits and widely used in the community as one of the traditional medicines. Annona muricata itself contains a compound known as acetogenin toxic if consumed continuously, In addition to the benefits so many of Annona muricata can give side effects to the body one of which is the part of the brain is called the gyrus dentatus. Anonaine, compound acetogenin could induce Bax expression in cancer cells resulting in apoptosis. This study wanted to find out if Annona muricata can induce Bax expression of neuron hippocampus gyrus dentatus female rats (rattus nervous). The purpose of this study was to subchronic effect of aqueous extract of soursop leaves (Annona muricata L.) Bax expression of neuron rat hippocampus gyrus dentatus(Rattus norvegicus). This study was a simple experimental study design using a post-test control group design to see Bax expression of neuron rat hippocampus gyrus dentatus (Rattus norvegicus) in subchronic administration of aqueous extract of soursop leaves (Annona muricata L.). The subjects were adult female rats (Rattus norvegicus) that met the inclusion criteria. The samples were 10 rats. Subjects were divided into 2 groups and each group consisted of 5 rats.